Delineation of functional roles of parasite-specific inserts in the malarial S-adenosylmethionine decarboxylase / ornithine decarboxylase - Louw, Abraham Izak (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.